Speckle noise reduction in medical ultrasound RF raw images - Santo, Verónica (2019)
Ultrasonography is the commonly used imaging modality for the examination of several pathologies due to its non-invasiveness,affordability and easiness of use. However, ultrasound images are degraded by an intrinsic artifact called 'speckle', which is the result of the constructive and destructive coherent summation of ultrasound echoes.This paper aims to generate B-mode images out of radiofrequency (RF) data following standard procedures,a series of steps such as envelope detection, log-compression and scan conversion. The best set of parameters of this pipeline will be selected in order to achieve B-mode images with high quality.